PM2.5 emissions and source profiles from open burning of crop residues. (November 2017) - Ni, Haiyan; Tian, Jie; Wang, Xiaoliang; Wang, Qiyuan; Han, Yongming; Cao, Junji; Long, Xin; Chen, L.-W. Antony; Chow, Judith C.; Watson, John G.; Huang, Ru-Jin; Dusek, Ulrike
Abstract: Wheat straw, rice straw, and corn stalks, the major agricultural crop residues in China, were collected from six major crop producing regions, and burned in a laboratory combustion chamber to determine PM2.5 source profiles and speciated emission factors (EFs). Organic carbon (OC) and water-soluble ions (the sum of NH4 +, Na +, K +, Mg 2+, Ca 2+, Cl −, NO3 − and SO4 2− ) are major constituents, accounting for 43.1 ± 8.3% and 27.4 ± 14.6% of PM2.5, respectively. Chloride (Cl − ) and water-soluble potassium (K + ) are the dominant ionic species, with an average abundance of 14.5 ± 8.2% and 6.4 ± 4.4% in PM2.5, respectively. The average K + /Cl − ratio is ∼0.4, lower than 2.8–5.4 for wood combustion. Similarity measures (i.e., Student's t -test, coefficient of divergence, correlations, and residual to uncertainty ratios) show the crop profiles are too similar for the species measured to be resolved from one another by receptor modeling. The largest difference was found between rice straw and corn stalk emissions, with higher OC and lower Cl − and K + abundances (50%, 8%, and 3% of PM2.5, respectively) for corn stalks; lower OC, and higher Cl − and K + abundances (38%, 21%, and 10% of PM2.5, respectively) for rice straw. Average EFs were 4.8 ± 3.1 g kg −1 for OC, 1.3 ± 0.8 g kg −1 for Cl − and 0.59 ± 0.56 g kg −1 for K + . Flaming and smoldering combustions resulted in an average modified combustion efficiency (MCE) of 0.92 ± 0.03, and low elemental carbon (EC) EFs (0.24 ± 0.12 g kg −1 ). OC/EC ratios from individual source profiles ranged from 12.9 ± 4.3 for rice straw to 24.1 ± 13.5 for wheat straw. The average K + /EC ratio was 2.4 ± 1.5, an order of magnitude higher than those from residential wood combustion (0.2–0.76). Elevated emission rates were found for OC (387 Gg yr −1 ) and Cl − (122 Gg yr −1 ), accounting for 44% and 14% of 2008 PM2.5 emissions in China. Highlights: Source profiles and EFs of crop residue open burning specific to China were determined. No significant differences existed in profiles for the same crop from different producing areas. No significant differences were found in profiles among different type of crops. Potassium and chloride were major ions emitted from crop residue burning. PM2.5 and its major component emissions from crop residue open burning for 2008 were estimated.